Impact of level of nutritional dose and diet specific components of colostrum in promoting 24 h gain, circulating lipid profile, and circulating levels of immunocrit, proteins, glucose, and free amino acids in neonatal gilt piglets - Linda M. Beckett; Wonders Ogundare; Leriana Garcia Reis; KaLynn Harlow; Addison Hill; Michayla Dinn; Emma Shelton; Evy Tobolski; Caeden Meade; Yu Han-Hallett; Christina Ramires Ferreira; Kara Stewart; et al. (PLoS ONE, 2026)
Colostrum (COL) intake relates to growth trajectory of pigs, which may be driven by differences in nutrient level, bioactive factors, or both. This study’s objective was to determine the effect of feeding COL versus milk replacer (MR) at high and low doses [20% or 10% of birth body weight (BBW)] on 24 h weight gain, body temperature, circulating levels of glucose, protein, immunocrit, free amino acids, lipids and small metabolites. At birth, gilt piglets (n = 57) were assigned to: pooled COL fed at 20% (COL20) or 10% of BBW (COL10); MR fed at 20% (MR20) or 10% of BBW (MR10); stay on sow (SOS) to suckle COL; or immediately euthanized at birth (zero hour; ZH). COL20, COL10, MR20, and MR10 were bottle fed diets every 2 h for 24 h, then piglets were euthanized, and blood collected. Serum samples were analyzed for glucose and protein using a colorimetric assay, immunocrit using the immunocrit ratio, free amino acids using liquid chromatography mass spectrometry, and lipidome using multiple reaction monitoring profiling. Dose affected glucose ( P = 0.02), being greater in 20% treatments than 10%. Diet and dose impacted immunocrit ( P < 0.0001) and protein ( P = 0.04), being highest in COL20, intermediate in COL10, and lowest in MR treatments. Diet type impacted all free amino acids ( P < 0.05). Diet and dose impacted concentration of triacylglycerols ( P = 0.0003), cholesterol esters (diet P = 0.001; dose P = 0.05), and only diet impacted phospholipids ( P = 0.04). Diet impacted individual triacylglycerol profile, with fatty acids longer and more unsaturated in COL than MR. Piglets on SOS, COL20, MR20 gained weight and maintained rectal temperature, whereas COL10 and MR10 lost weight and had lower temperatures ( P < 0.05). These data and previous studies indicate colostral proteins remain intact post-absorption preventing use for energy. Due to relatively high lactose in MR and circulating metabolite profiles, we postulated piglets fed MR prioritized glycolysis to support growth, whereas COL-fed depended on fatty acid oxidation. Further studies are warranted to understand how absorptive and post-absorptive metabolism respond to diet type and dose and contribute to circulating profiles of nutrients and metabolites.